Charlotte Pakins Cu’l Man Female Physiological Problems in Yellow Wallpaper and Man Made World, Female Behaviour: Exploring the Madness of Female Protagonists in American Literature (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper attempts to yield a critical reading of “The Yellow Wallpaper” (1892), which is one of the pioneering feminist works of American literature. Attempts have been made at finding affinities between the specific characterization of the story and the stereotypical male and female figures as defined by patriarchy and in terms of traditional gender roles. The paper tries to draw on Lacan’s conceptions of language, Cixous’ ideas about écriture féminine, and Freud’s misconception about women’s conditions. Drawing critical attention to this information, the paper focuses on the main unnamed female character and the fact that her anonymity helps the readers, specifically female readers, to identify themselves with her. This paper looks into the lives of the female protagonists in Charlotte Perkins Gilman’s “The Yellow Wallpaper,” Doris Lessing’s “To Room Nineteen,” and Khairiya Saqqaf’s “In a Contemporary House” in an attempt to reach a better understanding of women’s “madness.” To that end, this paper investigates the possibility of madness not being entirely a breakdown, but also a breakthrough, by analyzing the lives and experiences of the “mad” protagonists, as represented in the selected literary works, in light of R. D. Laing’s theories on the divided self and the politics of individual experiences. Despite the difference in time, place, and cultural contexts, all three women share the same experience of home confinement and domestication for different reasons that stem from patriarchal and social constraints. Such circumstances eventually lead these women to embrace forms of “madness” in ending a suffocating existence that does not allow them to connect with their inner-selves.